SPECIFICITIES AND IMPROVEMENTS OF APPLYING COOPERATIVE LOCALIZATION IN 5G - Antsa Nantenaina Randrianarison; Hajasoa Malalatiana Ramafiarisona (International Journal of Innovations in Engineering Research and Technology, 2023)
In this article, we want to emphasize the techniques and characteristics of cooperative localization applied to 5G. The concept of cooperative localization was first proposed by U.S. Air Force researchers in the early 2000s. It was developed as a way to improve the accuracy of positioning systems by using multiple sensors to estimate a position. The technique has since been applied to a variety of applications, including robotics, navigation, and autonomous vehicles. This type of localization based on device-to-device communication is garnering more and more interest with the arrival of the 5G network. The 5th generation has many features that allow for enhanced localization results. So, the main objective is to enhance the accuracy of position estimation. Cooperative localization is an emerging technology that relies on the use of multiple nodes to localize a target in a three-dimensional space. Cooperative localization leverages the use of distributed nodes to collect data from the target and then triangulate the target’s position. The nodes then transmit the data to a central server, which can then calculate the target’s exact location. Cooperative localization is becoming increasingly important in 5G networks due to its ability to improve network reliability and accuracy. There are many techniques and methods that can be used, including MultiDimensional Scaling and CrossOver – Multiple Way Ranging which we are particularly interested in. Unlike traditional localization techniques such as simple device to device communication or global positioning system that use at most two or three reference nodes, cooperative localization can be based on even more nodes of different types.